2017
DOI: 10.1016/j.ultrasmedbio.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

WFUMB Guidelines and Recommendations on the Clinical Use of Ultrasound Elastography: Part 5. Prostate

Abstract: The World Federation for Ultrasound in Medicine and Biology (WFUMB) has produced guidelines for the use of elastography techniques, including basic science, breast, liver and thyroid elastography. Here we present elastography in prostate diseases. For each available technique, procedure, reproducibility, results and limitations are analyzed and recommendations are given. Finally, recommendations are given based on the level of evidence of the published literature and on the WFUMB expert group's consensus. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 82 publications
(214 reference statements)
0
121
0
7
Order By: Relevance
“…The summary sensitivity was 81% (95% CI: 71-88) and the specificity was 91% (95% CI: [83][84][85][86][87][88][89][90][91][92][93][94][95][96] for the prediction of significant liver fibrosis. Subgroup analysis revealed that 2D-SWE had an excellent diagnostic performance according to each degree of liver fibrosis.…”
Section: Technical Success Rates Of Liver Stiffness Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The summary sensitivity was 81% (95% CI: 71-88) and the specificity was 91% (95% CI: [83][84][85][86][87][88][89][90][91][92][93][94][95][96] for the prediction of significant liver fibrosis. Subgroup analysis revealed that 2D-SWE had an excellent diagnostic performance according to each degree of liver fibrosis.…”
Section: Technical Success Rates Of Liver Stiffness Estimatesmentioning
confidence: 99%
“…Real-time elastography (RTE) has been used mainly for the evaluation of the pancreas [83][84][85][86], the thyroid [87][88][89][90][91][92][93][94], the prostate [95], the breast [5,96] but also for the liver [1,2,7,97]. Published evidence in children is scarce and contradictory [98][99][100].…”
Section: Strain Imaging (Real-time Elastography (Rte))mentioning
confidence: 99%
“…Practitioners need to be competent in the intravenous administration of contrast agents, be familiar with contraindications and be able to manage any possible adverse effects within the medical and legal framework of their country [4,38]. We refer to the educational activities of the collaborating societies of this paper, the World Federation of Ultrasound in Medicine and Biology (WFUMB) [9,23,[93][94][95][96][97][98][99][100][101][102], the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) [1,3,4,11,37,38,49,50,74,79,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] and the CEUS LI-RADS Working Group for Liver Imaging Reporting and Data System (LI-RADS®) [34][35][36][120]…”
Section: Education Qualificationmentioning
confidence: 99%
“…In addition to the WFUMB 2015 guidelines on elastography (basic principles [15], liver [17] and breast [16] more papers have been prepared and successfully published. The WFUMB guideline projects (steering committee: Richard Barr, David Cosgrove and Christoph F Dietrich) on prostate [56] and the The WFUMB guideline project on thyroid [57] have been both recently published. The same is true for the WFUMB position paper on point of care ultrasound [58].…”
Section: Student Committeementioning
confidence: 99%